Scope of practice distinctions based on primary work setting for genetic counselors in assisted reproductive technologies - Alyssa C. Snider, M.S., Ph.D., C.G.C; Lauren J. Isley, M.S., C.G.C; Lauri D. Black, M.S., C.G.C (Elsevier, 2021)
Objective: To elucidate the tasks within various work settings that assisted reproductive technologies (ART) genetic counselors believe to be within their scope of practice. Design: A survey was constructed and administered to genetic counselors who practice in the field of ART. Setting: Genetic counselors were asked to self-identify with a primary ART work setting: genetic testing laboratory (preimplantation genetic testing, carrier screening, or both), in vitro fertilization clinic, gamete donor agency, telegenetic practice (either private practice or telemedicine company), or other. Patient(s): N/A. Intervention(s): N/A. Main Outcome Measure(s): The number of years of practice in ART, tasks performed within various ART work settings representing the reality or the ideal, and perception of understanding of the scope of practice by nongenetics colleagues. Result(s): The majority of respondents reported <10 years of experience in this field. There were differences in what was considered the scope of practice among the various work settings. ART genetic counselors believed that their scope of practice was not well understood by their nongenetics colleagues. They also reported differences between the actual duties performed and what they ideally believed would be within their job function. Conclusion(s): The genetic counseling specialty of ART is a new work setting for genetic counselors. There is a need for education regarding the various roles of genetic counselors in ART. Better definition of the appropriate duties for genetic counselors in the various ART work settings is needed to foster effective working relationships with their nongenetics colleagues and optimize patient care.